2023
DOI: 10.3390/nu15071557
|View full text |Cite
|
Sign up to set email alerts
|

Combined Citrulline and Glutathione Supplementation Improves Endothelial Function and Blood Pressure Reactivity in Postmenopausal Women

Abstract: Postmenopausal women (PMW) may experience endothelial dysfunction associated with arginine (ARG) deficiency relative to asymmetric dimethylarginine (ADMA) caused by oxidative stress. Endothelial dysfunction contributes to increased blood pressure (BP) responsiveness to sympathoexcitation induced by the cold pressor test (CPT). We investigated the effects of citrulline alone (CIT) and combined with the antioxidant glutathione (CIT+GSH) on vascular function. Forty-four healthy PMW were randomized to CIT (6 g), C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Thus, it would be necessary to ingest 1·6–8·6 kg and 2·7–14·3 kg of watermelon flesh or rind per day to get 6 g and 10 g of CIT, respectively. We have reported increases in ARG levels after 6 g (43) and 10 g (20) of CIT for 4 weeks in postmenopausal women. However, serum ARG levels did not increase significantly with 2 g of CIT (43) .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, it would be necessary to ingest 1·6–8·6 kg and 2·7–14·3 kg of watermelon flesh or rind per day to get 6 g and 10 g of CIT, respectively. We have reported increases in ARG levels after 6 g (43) and 10 g (20) of CIT for 4 weeks in postmenopausal women. However, serum ARG levels did not increase significantly with 2 g of CIT (43) .…”
Section: Discussionmentioning
confidence: 87%
“…We have reported increases in ARG levels after 6 g (43) and 10 g (20) of CIT for 4 weeks in postmenopausal women. However, serum ARG levels did not increase significantly with 2 g of CIT (43) . Thus, CIT in the diet may have not affected the results of the present study.…”
Section: Discussionmentioning
confidence: 87%
“…Yet, the short-term supplementation period followed in our investigation may not suffice to induce these beneficial changes in blood pressure, pulse wave reflection, and arterial stiffness, as demonstrated in other L-citrulline studies with longer supplementation at rest or during disturbed hemodynamics [ 25 , 44 , 46 , 49 , 52 ]. Furthermore, a recent study by Figueroa et al [ 60 ] observed improvements in endothelial function in healthy postmenopausal women following four weeks of combined 2 g of citrulline with glutathione supplementation. In contrast, no changes were reported following 6 g of L-citrulline solely.…”
Section: Discussionmentioning
confidence: 99%
“…Several nutritional components have been studied, and their impact on endothelial function was demonstrated to be either positive (citrulline and glutathione [ 49 ]) or negative (α-ketoglutarate [ 50 ]).…”
Section: Impact Of Supplements On Ed In Dmmentioning
confidence: 99%